Analysis of a finite state multi-rotor dynamic inflow model - Prasad, J.V.R.; Kong, Y.-B.; Peters, D. (My University, 2017)
Finite state dynamic inflow models are able to compute rotor inflows with reasonable accuracy and has low computational requirements compared to high-fidelity Computational Fluids Dynamics (CFD). As such, they are often used to model rotor inflows in vertical lift vehicle flight simulation for performance and handling qualities evaluations. An extension of the Pressure Potential Superposition Inflow Model (PPSIM) to arbitrary number and arrangement of rotors in a multi-rotor aircraft is explored in this paper. Elements in the apparent mass matrix (M-matrix) and inflow influence coefficient matrix (L-matrix) are functions of separation distances between the rotors in any given configuration. Analysis of differences in steady-state rotor inflow distributions between PPSIM and isolated rotors is carried out. It has been shown that in hover, rotors with small longitudinal (lateral) clearance from one another affect the rotors’ inflow distributions, giving rise to fore-to-aft (side-to-side) gradient inflow components. In forward flight, the rotors’ wake are swept downstream and mainly affect inflows of rotors operating within the wake.